2019
DOI: 10.1177/0883073819856837
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Child Neurologists on Management of Pediatric Post-traumatic Headache

Abstract: Traumatic brain injury causes significant morbidity in youth, and headache is the most common postconcussive symptom. No established guidelines exist for pediatric post-traumatic headache management. We aimed to characterize common clinical practices of child neurologists. Of 95 practitioners who completed our survey, most evaluate <50 pediatric concussion patients per year, and 38.9% of practitioners consistently use International Classification of Headache Disorders criteria to diagnose post-traumatic hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
6
0
1
Order By: Relevance
“…This is consistent with a survey of pediatric PTH treatment that found most clinicians would wait 4 weeks or more after injury to start preventive medications. 25 Both the survey and this study found that the most popular prescription medications were tricyclic antidepressants, despite the facts that amitriptyline was not Downloaded From: https://jamanetwork.com/ on 03/15/2021 superior to placebo for pediatric migraine prevention 9 and may cause significant adverse effects.…”
Section: Discussionmentioning
confidence: 66%
“…This is consistent with a survey of pediatric PTH treatment that found most clinicians would wait 4 weeks or more after injury to start preventive medications. 25 Both the survey and this study found that the most popular prescription medications were tricyclic antidepressants, despite the facts that amitriptyline was not Downloaded From: https://jamanetwork.com/ on 03/15/2021 superior to placebo for pediatric migraine prevention 9 and may cause significant adverse effects.…”
Section: Discussionmentioning
confidence: 66%
“…35 The proper identification of posttraumatic headache and related symptoms may influence the treatments chosen for headache, which may include both abortive and prophylactic medications. 36 Other targeted therapies toward posttraumatic headache are based on contributors to headache provocation and include exercise, cervical physical therapy, and vestibular therapy. 37 The aggregation of symptoms of difficulty remembering, confusion, and difficulty concentrating into a Cognitive factor with the symptom of difficulty remembering as the greatest contributor highlights the need to address these cognitive factors in this student-athlete population.…”
Section: Discussionmentioning
confidence: 99%
“…Even in specialty concussion clinics, providers appear relatively reluctant to initiate headache specific treatment. We can see from Pearson et al [ 28 ] how providers are currently treating PTH in youth, with many physicians waiting to initiate therapy for 8 or even 12 weeks after injury. Popular treatments include vitamins/supplements, amitriptyline, and topiramate.…”
Section: Persistent Pth Treatment Modelsmentioning
confidence: 99%